Solid-phase methods for sequencing of nucleic acids I. Simultaneous sequencing of different oligodeoxyribonucleotides using a new, mechanically stable anion-exchange paper. - Rosenthal, A (1985)
A solid-phase method for simultaneous sequencing of large numbers of oligodeoxyribonucleotides has been developed using a new, mechanically stable anion-exchange paper. The excellent mechanical properties of the polymer allow the processing of several paper segments in one reaction vessel or to carry out all necessary operations on a larger area of the paper. In addition, DNA material can be chemically eluted from the new carrier during the piperidine reaction, thus avoiding salt elution of DNA and subsequent ethanol precipitation steps - a prerequisite for sequencing oligonucleotides. The approach involves 7 operations including: i) immobilization; ii) washing; iii) modification; iv) washing; v) sorting of the papers; vi) piperidine reaction and chemical elution and vii) lyophilization. All steps can be carried out in 4 to 5 hours independently of the number of oligonucleotides to be sequenced. It is also possible to sequence small oligonucleotides with 3 to 4 base pairs. The method can be fully automated.